Sistem Pendukung Keputusan Seleksi Penerimaan Karyawan Dengan Metode Analytical Hierarchy Process - Dudih Gustian; Maryam Nurhasanah; Muhammad Arip (Politeknik Caltex Riau, 2019)
The recruitment process is one of the routine activities undertaken by a company in fulfilling one of its targets and achievements. Therefore objective, transparent and professional recruitment process must be done for the fulfillment of human resources that comply with the required criteria. But this is sometimes not in accordance with expectations so that the company feels difficulties in placing employees as needed. This study used the Analytical Hierarchy Process method with several criteria including written test results, interviews, soft skills, Experience and Grooming. This research provides solutions for companies to facilitate the process of decision making precisely with the availability of accurate prospective employee data information, in order to comply with the criteria that the company needs, and can Subjeciating the recruitment process. The benefits are expected to get the criteri according to the needs of the company, and the selection of employees faster and precise in decision making on the destruction. This study resulted that by this method helps management in the process of selection of employees objectively with values of 0.21231, 0.21055, 0.21020, 0.18829 and 0.17865, which are tested from 5 new program candidates.